The Need for a Pacemaker after TAVI can be Influenced by Careful Planning and Predicted by Higher Troponin Values after Implantation Study: Z natančnim načrtovanjem implantacije lahko vplivamo na potrebo po srčnem spodbujevalniku po TAVI, to pa lahko predvidimo z vrednostjo troponina po posegu - Glavnik Poznič, Nina; Kanič, Vojko (Acta Medico-Biotechnica, 2026)
Aim: Conduction abnormalities that require the implantation of a permanent pacemaker (PM) are known to accompany transcatheter aortic valve implantation (TAVI). Specific patient-dependent and procedure-related features are known to correlate with higher pacemaker implantation rates. Methods: We analysed retrospective data from a single centre with 150 TAVI cases in 2023. Fourteen cases had a PM already implanted and two were excluded due to a change to surgery and repeated TAVI in the same month. Results: Two types of transcatheter heart valves (THVs) were implanted and chosen based on computer tomography scans. Nineteen patients (14%) required PM after TAVI and all underwent implantation in the same hospital. There was no difference in the type of THV implanted. Patients that required PM had preexisting right bundle branch block more frequently (20% vs. 9%, p = 0.355), but this was not significantly different. They had however, have significantly higher values of troponin (p = 0.012) and required longer hospitalisations (p = 0.007). On first outpatient control, patients with PM implants had an average of 95% of ventricular pacing, no difference in ejection fraction, and no difference in three month survival compared to patients without a PM implanted. Conclusions: The need for a PM after TAVI can be predicted and avoided to some point. Every TAVI procedure should be carefully planned. Well implanted PMs carry no risks for short term survival.
Keywords: transcatheter aortic valve implantation; pacemaker; conduction abnormalities; troponin; hospital stay; survival